Lecturers’ and Students’ Workbook Evaluation of English Proficiency Course at English Department of Universitas Negeri Padang - Marselina, Vivi; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
The aim of this study is to find out if the Cunningsworth theory is true and if the English Proficiency workbook can be used in the way it was meant to be used. This is what the descriptive quantitative method that uses equal random sampling does. A questionnaire was the main tool that the researcher used to properly gather the information they needed. Each participant had to pick one answer of eight different indicators. There was a total of 35 questions. One group of people who took part in the study was students in the English Department's English Proficiency course. Teachers and students who were interested in the subject were in this class. A study project is being worked on by 24 students and 5 teachers right now. 24 students crowded around the board where the discussion was taking place. Based on the results of the study, one could say that the workbook made did meet the requirements set by Cunningsworth. To be more specific, this is how things stand when it comes to meeting the needs of students, completing the program, and providing a wide range of learning materials.